Способ вывода из эксплуатации канального уран-графитового ядерного реактора - Гаврилов П. М. Петр Михайлович; Кудрявцев Е. Г. Евгений Георгиевич; Антоненко М. В. Михаил Викторович; Устинов А. А. Александр Алексеевич; Зяпаров И. Р. Ильдар Рахимович; Пешков С. Е. Сергей Евгеньевич; Горобченко А. Д. Александр Дмитриевич
опубл. 10.03.12